Handbook of research on global competitive advantage through innovation and entrepreneurship - Farinha, Luis M. Carmo, 1975- (Advances in business strategy and competitive advantage., 2015)
"This book explores the emergence of new ideas and opportunities in various markets and provides organizational leaders with the tools they need to take full advantage of those opportunities, focusing on economic growth in a fast-paced environment"--